Influence of preoperative docetaxel, cisplatin, and 5-fluorouracil on the incidence of complications after esophagectomy for resectable advanced esophageal cancer. Issue 4 (1st June 2014) - Yoshida, N.; Watanabe, M.; Baba, Y.; Ishimoto, T.; Iwagami, S.; Sakamoto, Y.; Miyamoto, Y.; Karashima, R.; Baba, H.
Summary: A limited number of patients with resectable advanced esophageal cancer can be cured by surgery alone. Although a regimen that consists of docetaxel, cisplatin, and 5-fluorouracil (DCF ) is a potential preoperative chemotherapy (PCT ) option for squamous cell carcinoma of the esophagus, the influence of DCF on subsequent esophagectomies remains unclear. A total of 80 patients who received preoperative DCF chemotherapy, and 174 patients who did not receive any preoperative treatment were retrospectively analyzed. There were no treatment-related deaths. No delays in surgery due to adverse events related to DCF were reported. Although patients who received PCT had significantly more advanced cancers and worse preoperative conditions, the incidence rates of complications did not increase. Although the frequency of severe complications was significantly higher in patients who received PCT, this treatment was not an independent factor for the occurrence of severe complications. PCT with DCF did not negatively affect subsequent esophagectomies with regard to the frequency of complications.